Proceedings of the 15th ACM International Conference on Multimedia 2007
DOI: 10.1145/1291233.1291284
|View full text |Cite
|
Sign up to set email alerts
|

Interactive video browsing on mobile devices

Abstract: Today, videos can be replayed on modern handheld devices, such as multimedia cellphones and personal digital assistants (PDAs), due to significant improvements in their processing power. However, screen size remains a limiting resource making it hard, if not impossible to adapt common approaches for video browsing to such mobile devices. In this paper we propose a new interface for the pen-based navigation of videos on PDAs and multimedia cellphones. Our solution -called the MobileZoomSlider -enables users to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Many browsing tools, with better interaction means than provided by a typical video player, have been presented in the literature (for a detailed review see [29]). While many of them are advanced navigation methods (e.g., [7,8]), extended video players (e.g., [10,14,18]) or enhanced video content visualizations [6], some are highly sophisticated browsing tools (e.g., [1,25,30]). These sophisticated tools provide very specific interfaces and advanced interaction methods, such as combined mouse/keyboard interaction for 3D navigation, table-of-content navigation in videos, navigation trees and spatial interaction (e.g., [12,13,22,23,26,28]).…”
Section: Introductionmentioning
confidence: 99%
“…Many browsing tools, with better interaction means than provided by a typical video player, have been presented in the literature (for a detailed review see [29]). While many of them are advanced navigation methods (e.g., [7,8]), extended video players (e.g., [10,14,18]) or enhanced video content visualizations [6], some are highly sophisticated browsing tools (e.g., [1,25,30]). These sophisticated tools provide very specific interfaces and advanced interaction methods, such as combined mouse/keyboard interaction for 3D navigation, table-of-content navigation in videos, navigation trees and spatial interaction (e.g., [12,13,22,23,26,28]).…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of our concept for video browsing on traditional desktop PCs has been evaluated in [3] and [4]. An evaluation of the PDA version described here can be found in [5]. An initial user study with 20 participants confirmed our statement that operation of the interface is easy and intuitive despite its complexity and the variety of offered interaction styles.…”
Section: Resultsmentioning
confidence: 60%
“…Hürst et al proposed the Mobile ZoomSlider interface [2] for stylus-based navigation on handheld devices. The basic idea is a virtual seeker-bar that can be used at any screen position.…”
Section: Related Workmentioning
confidence: 99%
“…In a recent work that builds on the idea of [6] and [2], we also proposed to use wipe gestures for navigation in videos on mobile devices instead of navigation with seeker-bars [8]. The idea in this work was to use simple wipe gestures for navigation in videos, as also used on touch-based devices for inspection of photo collections, documents, or slides of a presentation.…”
Section: Related Workmentioning
confidence: 99%